Derajat Ploidi Jahe Merah (Zingiber officinale Roxb. var. rubrum Rosc.) Hasil Induksi Dengan Kolkisin - Meiliana Friska; Budi Setiadi Daryono (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
Red ginger (Zingiber officinale Roxb. var. rubrum Rosc.) is one of the herb plants that often being used as a spice, traditional medicines, sweets, drinks, and material export commodities. The ginger’s rhizome is the most common because it is good for health freshness, and spice for food. The spicy from the ginger comes from ketone compounds ‘gingerol’. This research aims to produce polyploidy crops in red ginger by observing the changes of phenotype characters on the leaves, stems and rhizome resulted from colchicine induction. This research was based on experimental method with Randomized design with two factors, which were colchicine concentration (0,05%, 0,1% and 0,2%) and incubation time (6, 12 and 24 hours). Ploidy level was observed using flow cytometry technique. The data were analyzed using Analysis of Variance (ANOVA) and statistical data processing was done using F test at α = 5%. If the result shows any significant differences then was followed with Duncan Multiple Range Test (DMRT). The results showed that the change in the ploidy degree of red ginger was seen in K1W2 (0,05 % concentration of incubation time 12 hours) with increasing in ploidy from the diploid (2n) to mixoploid (2n= 2x+4x).